Impact of parathyroid Hormone’s dose, timing, and delivery mode on osteoclastogenesis and osteogenesis using a human periodontal ligament fibroblast model - Talbi, Wael M. I.; Steemers, Elizabeth; Hogervorst, Jolanda M. A.; Schoenmaker, Ton; de Vries, Teun J. (Frontiers in Pharmacology, 2025)
Bone drug parathyroid hormone (PTH or teriparatide) has dual functions: it is a widely used anabolic drug resulting in increased bone formation, but it also activates osteoclasts. To further investigate the mechanistic insight of dose, timing, and delivery mode, a suitable cell model, periodontal ligament fibroblast (PDLF), was used to study PTH’s role in osteoclastogenesis and osteogenesis. PDLF were either co-cultured with peripheral blood mononuclear cells (PBMC) to study osteoclastogenesis or cultured under osteogenic conditions to study osteogenesis. A PTH titration (10–12 to 10–9 M) for 3 weeks identified the optimal PTH dose. Optimal PTH (10–9 M) dose was then administered under six regimens: continuous, first week only, second week only, third week only, and intermittent. At day 21, outcomes included osteoclast number and multinuclearity, gene expression (qPCR) for osteoclastogenesis and alkaline phosphatase (ALP) activity, and Alizarin Red staining for osteogenesis. PTH enhanced osteoclast formation in a dose-dependent manner (p = 0.008), with 10–9 M being most effective. Timing was critical: first- and second-week exposure significantly increased osteoclast number and size, while continuous or late exposure had minimal effect. Larger osteoclasts, with >5 nuclei per osteoclast, were absent in the controls and exclusively present in all PTH-treated conditions. M-CSF and DC-STAMP expression aligned with osteoclastogenesis. Compared to t = 0 (without PBMC), the RANKL/OPG ratio increased in the second-week exposure group and intermittent groups. IL-1β was upregulated, strongest in the second-week exposure group (p < 0.01). Osteogenic effects were modest and donor-dependent; ALP activity was comparable across groups, though a significant decrease was found between the second week and intermittent regimens. Mineralization varied strongly between donors, with responders and non-responders to PTH treatment. PTH exerts time-dependent effects on osteoclastogenesis in human co-cultures, particularly during early phases. Osteogenic responses varied, suggesting a complex interplay of timing, cell context, and donor variability. These findings support further investigation into optimized timing and delivery of PTH in periodontal regeneration.